2017
DOI: 10.26891/jik.v8i1.2014.18-24
|View full text |Cite
|
Sign up to set email alerts
|

Profil Pengendalian Diabetes Melitus Tipe 2 Di Poliklinik Penyakit Dalam RSUD Arifin Achmad Pekanbaru

Abstract: Management in patients with type 2 diabetes mellitus (DM) is aimed diabetic control required antidiabetic drugs(OAD). The aim of this study was to know data about the profile of diabetics control in patients with type 2 diabetesmellitus followed in department of endocrinology Arifin Achmad General Hospital Pekanbaru. The type of researchwas descriptive. The samples are 96 people included all patients with type 2 DM according to inclusion criteria. Theidentity patients and patients knowledge were determined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
2
0
5
Order By: Relevance
“…Hasil penelitian ini sesuai dengan penelitian Romadhiati tahun 2006 di RSUD Arifin Achmad Pekanbaru periode 2003-2004, dilaporkan bahwa persentase nilai HbA1c ≥ 6,5 pada perempuan (56,7%) lebih tinggi dari laki-laki (21). Demikian pula penelitian Lesi Kurnia Putri yang dilakukan tahun 2012 di RSUD Arifin Achmad Pekanbaru, menemukan bahwa persentase nilai HbA1c ≥ 6,5 pada perempuan 58,3% lebih tinggi dari laki-laki (22) . Selain itu Chen etal dari hasil penelitian di Taiwan juga menemukan bahwa persentase nilai HbA1c ≥ 6,5 pada perempuan 66,7% lebih tinggi dari laki-laki (23) .…”
Section: Bahan Dan Metodeunclassified
“…Hasil penelitian ini sesuai dengan penelitian Romadhiati tahun 2006 di RSUD Arifin Achmad Pekanbaru periode 2003-2004, dilaporkan bahwa persentase nilai HbA1c ≥ 6,5 pada perempuan (56,7%) lebih tinggi dari laki-laki (21). Demikian pula penelitian Lesi Kurnia Putri yang dilakukan tahun 2012 di RSUD Arifin Achmad Pekanbaru, menemukan bahwa persentase nilai HbA1c ≥ 6,5 pada perempuan 58,3% lebih tinggi dari laki-laki (22) . Selain itu Chen etal dari hasil penelitian di Taiwan juga menemukan bahwa persentase nilai HbA1c ≥ 6,5 pada perempuan 66,7% lebih tinggi dari laki-laki (23) .…”
Section: Bahan Dan Metodeunclassified
“…Patients and their families are entitled to get knowledge and education about the course of the disease, prevention, complications, and management of DM [22,23] . Adherence in patients with type 2 diabetes is generally defined as the level of behavior of someone who is getting treatment for diet, taking medication and carrying out a lifestyle in accordance with the recommendations of health care providers [24] Patients who do not understand DM, often do not comply with DM treatment [25] The success of DM treatment is highly dependent on the patient's compliance with taking medication. Several previous studies on the relationship between knowledge and adherence to taking medication have shown different results [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Insulin memiliki peran penting dalam metabolisme lemak dan karbohidrat di jaringan hepar dan lemak. 14 Hasil kadar HDL pada pasien DM Tipe 2 di RSUD Subang pada kelompok tinggi atau  60 mg/dL yaitu 18 orang (58,0%). Penelitian sesuai dengan Kurnia 2019 yang menggambarkan kadar HDL lebih dominan tinggi atau >60 mg/dL pada pasien DM tipe 2 di RSUD Cilegon.…”
Section: Pembahasanunclassified